Our people, our resources : Supporting rural communities in participatory action research on population dynamics and the local environment - Barton, Thomas George; Borrini-Feyerabend, Grazia; Sherbinin, Alex De.; Warren, Patrizio (Gland, Switzerland : IUCN--the World Conservation Union, 1997)
This handbook illustrates concepts, methods and tools for "primary environmental care", an approach that seeks to empower communities to meet basic needs while protecting the environment. In particular, it focuses on how population size, structure, growth (or decline) and movements relate to the quality of the environment and the quality of life. Emphasis is placed on a community-led process of participatory action research in which local knowledge and skills are fully utilized. A main purpose is to promote the effective, integrated management of environment and population dynamics for the benefit of local people. As a collection of tools for action, it is designed for professionals in conservation and natural resource management, development, population and public health who wish to promote and assist participatory action research in rural communities.
Includes bibliographical references (p. 245-257).
Keywords: Rural development -- Environmental aspects -- Developing countries; Community development -- Environmental aspects -- Developing countries; Natural resources -- Developing countries; Population geography; Human geography; Rural development